(untitled) (Mugda Medical College Journal, 2025)
Tubercular cholecystitis is an extremely rare form of abdominal tuberculosis. It is a rare entity that often masquerading as chronic cholecystitis. We report a case of a 40-year-old male hospitalized with chronic upper abdominal pain, fever, and cough and subsequently diagnosed as a case of chronic cholecystitis through routine investigations and imaging procedures in a private medical college hospital in Bangladesh. Histopathological examination after cholecystectomy revealed classical features of tuberculosis including granulomas with caseous necrosis and Langhans giant cells. The patient was initiated on anti-tubercular therapy postoperatively and showed excellent recovery. To our knowledge, there are very few reported cases of gallbladder tuberculosis from Bangladesh, particularly from private medical hospital settings. This case underscores the importance of considering tuberculosis in gallbladder pathology in endemic areas. Early recognition and initiation of antitubercular therapy lead to an excellent patient outcomes. Mugda Med Coll J. 2025; 8(1): 69-71